Pengaruh Disiplin dan Motivasi Kerja Terhadap Kinerja Karyawan Pada CV. Legenda Timur Indonesia Bandung - Misja Misja; Rosento Rosento (Prisani Cendekia, 2023)
Employee performance is an important factor in the success of a company. However, employee performance is not always stable and can be influenced by various factors, such as discipline and work motivation. Work discipline includes employee obedience to work rules and procedures, while work motivation includes the desire of employees to do a good job. Therefore, this study aims to evaluate the effect of discipline and work motivation on employee performance. Concerning the problem of employee performance is also caused by the low motivation received by employees. Amidst the workload owned by employees motivation is needed from a leader who can improve employee performance. The results of statistical tests prove that there is an influence between Discipline on Employee Performance. It can be seen from the results of data processing that the t count = count = 8.707 is greater than the t table = 0.681 and the significance value = 0.00 is smaller than 0.05 or 5% then H0 is rejected Ha is accepted. It can be concluded that discipline has a positive and significant partial effect on employee performance at CV Legend Timur Indonesia with the value of the coefficient of determination shown on the F valuesquare is 0.666 meaning that the effect of Discipline on Employee Performance is 66.6%.